Performing Religion and Spirituality: The Postsecular Turn in Contemporary British and Irish Theatre - Cummins, Miriam (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2022)
This thesis argues that there has been a postsecular turn on the contemporary stage, focussing in particular on woman-centred theatre in Britain and Ireland in the past three decades. It deals with the representation of the female body in Christianity in a 2007 revival of Saint Joan by Bernard Shaw and The Testament of Mary (2014) by Colm Tóibín, the portrayal of the Magdalene laundry in Eclipsed (1992) and Stained Glass at Samhain (2002) by Patricia Burke Brogan as well as Laundry (2011) by ANU Productions, and the controversy surrounding the Islamic headscarf in Shades (2009) by Alia Bano and What Fatima Did… (2009) by Atiha Sen Gupta. It adopts a broad poststructuralist feminist approach, applying various lenses of postchristian feminism, postmodernism, and postcolonialism to plays that represent the postsecular. The primary method of analysis employed is textual analysis, but I have also conducted archival research and refer to aspects of performance including staging, casting, and reception where possible. The arguments in each chapter contribute to wider theoretical debates which are contextualized in the introduction to each chapter. Chapter 2 makes a case for the limits of postchristian feminism insofar as although it grants women bodily autonomy, the patriarchal power structure of Christianity remains intact. Chapter 3 argues that postmodernism is an extension rather than a disruption of modernism. Chapter 4 claims that the presence of the postcolonial Other in Europe in the form of Muslim immigrants represents an opportunity as much as it represents a threat to the idea of the secular European Self. This is the first full-length study to identify and analyse a postsecular turn in contemporary British and Irish theatre. It offers new readings of well-researched plays such as Shaw’s Saint Joan and ANU Productions’ Laundry as well as exploring under-researched plays including Alia Bano’s Shades and Atiha Sen Gupta’s What Fatima Did… While the affinities between the postsecular and the postmodern, and the postsecular and the postcolonial have been well expounded by John McClure, Mike King, Graham Huggan, and Bruce Robbins among others, this is also the first study to suggest a conceptual link between the postsecular and the post-Christian in theatre and performance.
APPROVED
Keywords: religion and spirituality; the postsecular turn; postsecular feminism; contemporary British and Irish theatre; woman-centred theatre; George Bernard Shaw; Colm T?ib?n; Patricia Burke Brogan; ANU Productions; Atiha Sen Gupta; Alia Bano